ETNOBOTANY OF PLANTS IN THE MANDAILING TRADITIONAL WEDDING SERVICE IN THE VILLAGE AROUND THE BATANG GADIS NATIONAL PARK AREA, MANDAILING NATAL REGENCY - Levia Febrialisti; Aswarina Nasution (JBIO: jurnal biosains (the journal of biosciences), 2022)
This study aims to document belief systems, local knowledge systems, plant utilization practices, and find out the cultural importance or ICS of plant species used in traditional Mandailing wedding ceremonies in villages around the TNBG area. The research method is qualitative and quantitative. Data was collected through semi-structured interviews, participatory observation, documentation, focus group discussions (FGD), collection of plant samples and making herbarium. The plants used in the traditional Mandailing wedding ceremony are 43 species which are included in 20 plant families. Plants with high ICS value were found in burangir (Piper betle L.), sontang (Uncaria rhynchophylla Miq.), pining (Areca catechu L.), and timbako (Nicotiana tabacum L.) with an ICS value of 96.